Penyertaan dalam program pembangunan diri dikalangan staf sokongan sector awam - Daisy, Mandai, (Universiti Malaysia Sarawak (UNIMAS), 2004)
The purpose of this study is to determine the participation in self development program among the supportive staff at Natural Resources and Environment Board (NREB). The objective ofthis study is to determine the participation level in selfdevelopment program and identify the factors influencing this participation. This study used survey methodology and questionnaire to collect information from the 55 samples in various departments at NREB. The statistic analysis that was used in this study was t test, ANOVA, and Pearson correlation. The findings show that majority of the supportive staffs have high participation level in se(( development program that is 81.82 percent. Only 18.18 percent supportive staffs have moderate participation level in self development program. There was no significant difference between male and female supportive staff, the staffs ofvarious age categorizes and staffs of various academic levels in terms of participation in se(( development program. Besides that, the findings also show there are sign(jicant relationships between the four factors (personal factors, career advancement, reward and social relationship factors) with the participation in self development program among the supportive staff. Based on this finding. management should put strong emphasis on these four factors in order to promote participation in selfdevelopment program among employees in their organization.